PENGARUH PROMOSI, ATRIBUT TOKO (STORE ATTRIBUTES), DAN INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA NICK COFFE DI KOTA BENGKULU - Munifah Khomilah (UM. Bengkulu, 2020)
This study aims to determine the effects of Promotions, Store Attributes, and Product Innovations on Repurchase Decisions on Nick Coffe in Bengkulu City. This research is a quantitative study with a sample of 96 respondents, using accidental sampling techniques. collection techniques using observation and questionnaires. Data analysis techniques using the classic assumption test, multiple linear regression, coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression tests using SPSS namely Y = 2.063 + 0.192X1 + 0.036X2 + 0.713X3. From the results of hypothesis testing that Promotion (X1) has a positive effect on Repurchase Decisions on Nick Coffe in Bengkulu City, with T test results showing a significance value of 0.000 <0.05, Store Attribute (X2) has a positive effect on Repurchase Decisions on Nick Coffe in Bengkulu City, with T test results showing a significance value of 0.037 <0.05, Product Innovation (X3) has a positive effect on Repurchase Decisions on Nick Coffe in Bengkulu City, with T test results showing a significance value of 0,000 < 0.05, Hypothesis testing of the T test and F test shows that Promotion, Store Attributes, and Product Innovation have a significant effect on Repurchase Decisions with a significance level <0.05. This means that Ho was refused Ha was accepted. In other words Promotions, Store Attributes, and Product Innovations have a significant effect both partially and simultaneously on Repurchase Decisions on Nick Coffe Customers. This is evidenced by the F test showing a significance value of 0.000 <0.05. Keywords: Promotion, Product Innovation and Purchase Decisions